A combination of hydroxytyrosol, omega-3 fatty acids and curcumin improves pain and inflammation among early stage breast cancer patients receiving adjuvant hormonal therapy: results of a pilot study - Martínez, N.; Herrera, M.; Frías, L.; Provencio, M.; Pérez-Carrión, R.; Díaz, V.; Morse, Michael; Crespo, M. C. (Clinical & translational oncology, 2019)
Purpose Breast cancer patients receiving hormonal therapies face risks of relapse, increased rates of cardiovascular events, and toxicities of therapy such as aromatase inhibitor (AI)-associated musculoskeletal symptoms (AIMSS). C-reactive protein (CRP), a marker for inflammation, is associated with breast cancer outcomes. We evaluated whether the olive-derived polyphenol hydroxytyrosol combined with omega-3 fatty acids and curcumin would reduce CRP and musculoskeletal symptoms in breast cancer patients receiving adjuvant hormonal therapies. Experimental design This prospective, multicenter, open-label, single arm, clinical trial enrolled post-menopausal breast cancer patients ( n = 45) with elevated C-reactive protein (CRP) taking predominantly aromatase inhibitors to receive a combination of hydroxytyrosol, omega-3 fatty acids, and curcumin for 1 month. CRP, other inflammation-associated cytokines, and pain scores on the Brief Pain Inventory were measured before therapy, at the end of therapy and 1 month after completion of therapy. Results CRP levels declined during the therapy [from 8.2 ± 6.4 mg/L at baseline to 5.3 ± 3.2 mg/L ( p = 0.014) at 30 days of treatment], and remained decreased during the additional 1 month off therapy. Subjects with the highest baseline CRP levels had the greatest decrease with the therapy. Pain scores also decreased during the therapy. There were no significant adverse events. Conclusions The combination of hydroxytyrosol, omega-3 fatty acids, and curcumin reduced inflammation as indicated by a reduction in CRP and reduced pain in patients with aromatase-induced musculoskeletal symptoms. Longer studies comparing this combination to other anti-inflammatories in larger groups of patients with clinical outcome endpoints are warranted.